Burden of metabolic syndrome on primary healthcare costs among older adults: A cross-sectional study - Ricardo, Suelen Jane [UNESP] (2024)
BACKGROUND: The impact of metabolic syndrome (MetS) on healthcare costs remains unclear in the literature. OBJECTIVES: To determine the impact of MetS on primary healthcare costs of adults, as well as to identify the impact of physical activity and other covariates on this phenomenon. DESIGN AND SETTING: This cross-sectional study was conducted in the city of Presidente Prudente, State of São Paulo/Brazil, in 2016. METHODS: The sample comprised 159 older adults (> 50 years) of both sexes (110 women) who were identified from their medical records in the Brazilian National Health Service. Healthcare costs (US$) were assessed through medical records and divided into medical consultations, medications, laboratory tests, and total costs. MetS was assessed using medical records. RESULTS: The Brazilian National Health Service spent more on consultations (US$ 22.75 versus US$ 19.39; + 17.3%) and medication (US$ 19.65 versus US$ 8.32; + 136.1%) among adults with MetS than among those without MetS, but the costs for laboratory tests were similar (P = 0.343). Total costs were 53.9% higher in adults with MetS than in those without the diagnosis of the disease (P = 0.001). Regarding total costs, there was an increase of US$ 38.97 when five components of MetS were present (P = 0.015), representing an increase of approximately 700%, even after adjusting for sex, age, and physical activity. CONCLUSION: In conclusion, the presence of the MetS is responsible for increasing primary care costs among older adults, especially in those related to medicines.